2021
DOI: 10.1101/2021.03.17.435757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular characterization reveals genomic and transcriptomic subtypes of metastatic urothelial carcinoma

Abstract: Metastatic urothelial carcinoma (mUC) is a lethal cancer for which few therapeutic options exist. To define the molecular landscape of mUC and to identify targets for therapy, we performed whole genome DNA- and RNA-sequencing on fresh-frozen metastatic tumor biopsies of 116 mUC patients. Driver genes resembled those reported for primary UC; yet, three putative driver genes unique to mUC were identified: CNTNAP5, RARG and MGP. Consensus clustering based on mutational signatures revealed two major genomic subtyp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…Genomic analyses of bladder cancer of various stages and grades have shown that bladder cancer is a heterogeneous disease of which the high mutation burden is largely driven by activation of APOBEC mutagenesis (Lawson et al 2020;Nakauma-González et al 2021;Robertson et al 2018). Molecular characterization revealed activating FGFR3 alterations in ~16% of the samples, with a higher prevalence in non-muscle invasive bladder cancer (Cancer Genome Atlas Research Network 2014; Robertson et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic analyses of bladder cancer of various stages and grades have shown that bladder cancer is a heterogeneous disease of which the high mutation burden is largely driven by activation of APOBEC mutagenesis (Lawson et al 2020;Nakauma-González et al 2021;Robertson et al 2018). Molecular characterization revealed activating FGFR3 alterations in ~16% of the samples, with a higher prevalence in non-muscle invasive bladder cancer (Cancer Genome Atlas Research Network 2014; Robertson et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Genome analyses of bladder cancer of various stages and grades have shown that bladder cancer is a heterogeneous disease of which the high mutation burden is largely driven by activation of APOBEC mutagenesis [115][116][117] . Molecular characterization revealed in 16-17% of the samples FGFR3 alterations, with higher prevalence in NMIBC 117,118 .…”
Section: Introductionmentioning
confidence: 99%